Size-dependent properties of matter: Is the size of a pill important?. (2nd October 2017) - Adadan, Emine; Akaygun, Sevil; Sanyal, Amitav
ABSTRACT: This interdisciplinary scientific inquiry lesson specifically utilizes the 5E learning cycle to engage high school students in an investigation on size-dependent properties of matter. In particular, this inquiry lesson focuses on a biologically relevant phenomenon, namely accessibility to a pharmaceutical drug with respect to the size of the pill. In this context, students design and conduct a controlled experiment to test how the accessibility to an encapsulated drug is affected by the change in the size of the pill. Thus, through this investigation, students not only learn about the relationship between the size of a material in terms of surface area-to-volume ratio and the rate of diffusion of molecules, but also extend this knowledge to the importance of size in the context of nanoscale. Additionally, students practice the science process skills involved in undertaking a scientific inquiry.